Ultra-High Field Magnetic Resonance Imaging of the Retrobulbar Optic Nerve, Subarachnoid Space, and Optic Nerve Sheath in Emmetropic and Myopic Eyes - Nguyen, Bao N. (Transl Vis Sci Technol, 2021)
PURPOSE: We aimed to image the optic nerve, subarachnoid space and optic nerve sheath in emmetropes and myopes ultra-high field (7-Tesla) magnetic resonance imaging (MRI). We targeted the retrobulbar distance of approximately 3 mm behind the eyeball, an area of clinical interest because of optic nerve sheath distensibility and pressure-related enlargement. METHODS: Eleven emmetropes (+0.75 to −0.50D, aged 20–41 years) and 10 myopes (−4.5 to −12D, aged 21–37 years) participated. Cross-sectional area of the optic nerve, subarachnoid space and optic nerve sheath at approximately 3 mm behind the eye were measured from two-dimensional T2-weighted coronal oblique MRI images obtained through the left optic nerve. Axial length of the left eye was measured from T2-weighted axial MRI images. In nine emmetropes and seven myopes, the optic nerve head was imaged with optical coherence tomography to compare retrobulbar and intraocular measures. RESULTS: Retrobulbar optic nerve, subarachnoid space and optic nerve sheath dimensions differed between myopes and emmetropes. Myopes tended to have smaller optic nerve and subarachnoid space. Longer MRI-derived axial length was associated with smaller optic nerve area (P = 0.03). Bruch's membrane opening area did not predict retrobulbar optic nerve area (P = 0.48). CONCLUSIONS: This study demonstrates the feasibility of using 7-Tesla MRI to measure optic nerve, subarachnoid space, and optic nerve sheath dimensions behind the eye. In healthy adults, the retrobulbar optic nerve and subarachnoid space size are influenced by the degree of myopia. TRANSLATIONAL RELEVANCE: ultra-high field MRI is a practical tool for assessing the morphometry of the optic nerve and surrounding anatomy behind the eye.